Literature Review: The Triage Optimization with Emergency Severity Index (ESI) Impact on Emergency Department Quality of Care - Mariana Mariana; Erna Melastuti; Dyah Wiji Puspita Sari; Indah Sri Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Emergency Departments are critical healthcare units where efficient triage plays an important role in ensuring optimal patient care. The Emergency Severity Index (ESI) is a widely used triage system designed to improve prioritization and resource allocation. Proper use of ESI-based triage will improve the quality of care. Objective: This literature review aims to analyze the impact of ESI-based triage optimization on Emergency Department service quality. Methods: A systematic search was conducted using Google Scholar, PubMed, ResearchGate, and SciSpace databases, using the keywords: Emergency Severity Index (ESI), Emergency Department, Triage, using the PCC (Population, Concept, Context) approach. The article selection process used PRISMA which was then subjected to critical appraisal. The initial search was conducted through Google Scholar (5,521 articles), PubMed (2,019 articles), ResearchGate (881 articles), and SciSpace (99 articles). The process of removing duplicate articles left 8,151 articles, the initial screening of 8,125 articles was eliminated, so only 26 articles entered the further screening stage. From this process, 16 articles did not meet the criteria and were excluded. Finally, 10 articles that met the inclusion criteria were selected and reviewed. Results: The findings showed that ESI optimization improved patient flow, reduced waiting time, and improved resource utilization, leading to better clinical outcomes and patient satisfaction. Conclusion: implementation of an optimized ESI-based triage system contributes significantly to the efficiency and quality of Emergency Department care, emphasizing the need for consistent training and protocol adherence.